Ultrathin, Molecular-Sieving Graphene Oxide Membranes for Selective Hydrogen Separation - Li, Hang; Song, Zhuonan; Zhang, Xiaojie; Huang, Yi; Li, Shiguang; Mao, Yating; Ploehn, Harry J.; Bao, Yu; Yu, Miao (Science (American Association for the Advancement of Science), 2013)
Ultrathin, molecular-sieving membranes have great potential to realize high-flux, high-selectivity mixture separation at low energy cost. Current microporous membranes [pore size < 1 nanometer (nm)], however, are usually relatively thick. With the use of current membrane materials and techniques, it is difficult to prepare microporous membranes thinner than 20 nm without introducing extra defects. Here, we report ultrathin graphene oxide (GO) membranes, with thickness approaching 1.8 nm, prepared by a facile filtration process. These membranes showed mixture separation selectivities as high as 3400 and 900 for H₂/CO₂ and H₂/N₂ mixtures, respectively, through selective structural defects on GO.